Effects of Hub-and-Spoke Free Trade Agreements on Trade: Panel Data Analysis - Joseph D. Alba; Jung Hur; Donghyun Park (Asian Development Bank (ADB), 2008)
Overlapping free trade agreements (FTAs) have given rise to hub-and-spoke FTAs that may promote trade by giving an export advantage to the FTA hub country. We empirically investigate the effect of hub-and-spoke FTAs on trade using panel data consisting of 99 countries and covering the period 1960–1999. Our empirical analysis of the panel data yields three notable findings. First, FTAs have a significant and positive impact on trade. Second, hub-and-spoke FTAs increase trade above and beyond FTAs, and thus reinforce the trade-boosting effects of FTAs. Third, our results imply an annual growth rate of 4.9% in bilateral trade and hence a doubling of trade after 14 years between FTA partners. Our results indicate that the hub-and-spoke nature of FTAs has a positive effect on trade, in addition to the direct, trade-liberalizing effect of FTAs. Therefore, in a world of overlapping FTAs, a more accurate empirical analysis of the relationship between FTAs and trade calls for taking into account the hub-and-spoke characteristic of FTAs.
hdl:11540/1781
Keywords: 330; Freihandelszone; Internationale Wirtschaft